2001
DOI: 10.1007/s11745-001-0736-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of prostaglandin H synthase activity by conjugated linoleic acid (CLA) and specific CLA isomers

Abstract: Conjugated linoleic acid (CLA) has been shown to inhibit tumorigenesis in animal models and is cytostatic to numerous cell lines in vitro. However, the mechanism of action is unknown. In the current study, we determined the effects of CLA and specific isomers of CLA on the rate of oxygenation of arachidonic acid by prostaglandin H synthase (PGHS) in ram seminal vesicle microsomes. The enzyme was incubated with 0.1 to 100 microM CLA or specific isomers of CLA for 2 min prior to the addition of 44 to 176 microM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…These 20-C metabolites of CLA have been recovered from livers of rats fed CLA (36). A more recent report also demonstrates inhibition of COX by various isomers of CLA (7). If COX inhibition is the method by which CLA is acting, we hypothesize that one or more enzymes in the lipoxygenase pathway are also being inhibited because rather than potentiation of the LT release [which is typically seen when COX alone is inhibited (19)], we showed that these mediators are also downregulated in CLA-fed animals.…”
Section: Discussionmentioning
confidence: 89%
“…These 20-C metabolites of CLA have been recovered from livers of rats fed CLA (36). A more recent report also demonstrates inhibition of COX by various isomers of CLA (7). If COX inhibition is the method by which CLA is acting, we hypothesize that one or more enzymes in the lipoxygenase pathway are also being inhibited because rather than potentiation of the LT release [which is typically seen when COX alone is inhibited (19)], we showed that these mediators are also downregulated in CLA-fed animals.…”
Section: Discussionmentioning
confidence: 89%
“…Although 10t,12c-CLA was shown to reduce COX-2 protein expression and PGE 2 release, the concentration to reduce protein expression was higher than that required to decrease PGE 2 release. CLA has been shown to be a direct inhibitor of COX-2 enzymatic activity (17,35; unpublished data) and to reduce arachidonic acid level in phospholipids through the inhibition of fatty acid elongase (36). Hence, 10t,12c-CLA-induced decreases in COX-2 product formation could be the results of 1) decreased COX-2 protein, 2) decreased substrate availability, and 3) decreased COX-2 activity.…”
Section: Discussionmentioning
confidence: 94%
“…The 9c,11t-isomer appears to be the most effective, followed by the 9c,11c-, the 10t,12c-, and finally the 9t,11t-isomers [10]). A related finding has been observed with the inducible cyclooxygenase (COX-2 of the PGHS-2 complex) of cultured murine RAW macrophages [51], where several CLA isomers (e.g.…”
Section: Synthesis Of Eicosanoidsmentioning
confidence: 88%